Extraction and Thin Layer Chromatography of Alkaloids from Bael (Aegle marmelos) Leaves - ,Madhukar S. Wadikar2 and Sunil U. Tekal, Vinod U. Borde1*, Prashant P. Pangrikar2 (Journal of Ecobiotechnology, 2011)
Bael tree, (Aegle marmelos, Family- Rutaceae), is a sacred tree widely grown in Indian forests, Ceylon, Burma, Thailand and Indo-China. All parts of the tree are used for medicinal purpose. Some of the medicinal properties are astringent, antidiarreal, antidystentric, demulcent, stromachic, fever curing, insulin-promoter, anti-inflammatory, cardio tonic and cures ophthalmic, urinary trouble, palpitation and many more. Most of these properties are believed to be due to presence of bioactive alkaloids in Bael. This study was carried out to develop an easy method of extraction and separation of alkaloids from dried Bael leaves. Alkaloids from the dried leaves of Bael were extracted in 95% ethanol and separated with chloroform in presence of synthetic antioxidants butylated hydoxytoluene (BHT and butylated hydroxyaniosole (BHA) by thin layer chromatography. BHT and BHA seem to protect alkaloids from their degradation/ conversion to other components.